2010
DOI: 10.1111/j.1601-183x.2010.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ras activation inhibits adult hippocampal progenitor cell division and impairs spatial short‐term memory

Abstract: A large number of endogenous and exogenous factors have been identified to upregulate and downregulate proliferation, differentiation and/or survival of newborn cells in the adult hippocampus. For studying neuronal mechanisms mediating the impact of those factors, we used a transgenic synRas mouse model expressing constitutively activated Valin12-Harvey Ras selectively in differentiated neurons. BrdU injections showed significantly reduced proliferation of new cells within the adult hippocampus of transgenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 76 publications
(102 reference statements)
0
23
0
Order By: Relevance
“…This has been demonstrated by BrdU-injections that revealed a lower number of BrdU-labeled cells 24 h after the last of 12 injections. A specific reduction of the newborn neuronal population has been confirmed by double labeling with neuron- and glia-specific markers and by a smaller number of doublecortin-positive cells (Table 1; Lafenêtre et al, 2010; Manns et al, 2010). This effect is exclusive for the adult hippocampus since generation of new cells within the subventricular zone is not affected (Manns et al, 2010).…”
Section: Neurogenesis Is Diminished In Synras Micementioning
confidence: 86%
See 3 more Smart Citations
“…This has been demonstrated by BrdU-injections that revealed a lower number of BrdU-labeled cells 24 h after the last of 12 injections. A specific reduction of the newborn neuronal population has been confirmed by double labeling with neuron- and glia-specific markers and by a smaller number of doublecortin-positive cells (Table 1; Lafenêtre et al, 2010; Manns et al, 2010). This effect is exclusive for the adult hippocampus since generation of new cells within the subventricular zone is not affected (Manns et al, 2010).…”
Section: Neurogenesis Is Diminished In Synras Micementioning
confidence: 86%
“…A specific reduction of the newborn neuronal population has been confirmed by double labeling with neuron- and glia-specific markers and by a smaller number of doublecortin-positive cells (Table 1; Lafenêtre et al, 2010; Manns et al, 2010). This effect is exclusive for the adult hippocampus since generation of new cells within the subventricular zone is not affected (Manns et al, 2010). Additionally, doublecortin immunolabeling also demonstrated impaired dendritic differentiation in neuronal precursor cells of synRas mice as indicated by smaller dendritic lengths and a lower number of dendritic segments (Lafenêtre et al, 2010).…”
Section: Neurogenesis Is Diminished In Synras Micementioning
confidence: 86%
See 2 more Smart Citations
“…It has been recently shown that the consolidation of long-term recognition memory is a circadian-regulated process, mediated by the Ras-inhibitory protein SCOP (62). On the other hand, synRas mice showed impaired spatial short-term memory associated also with a reduced proliferation of newborn cells in the dentate gyrus of the hippocampus (63, 64) and decreased short-term recognition memory (65, 66). All these studies suggest that modulation of Ras activity is critical for memory performance, but a question remains as to whether and how circadian regulation of Ras is associated in this process.…”
Section: Role Of Ras In Learning and Memory Consolidationmentioning
confidence: 99%